2018
DOI: 10.1016/j.jmb.2018.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of the BcsG Subunit of the Cellulose Synthase in Salmonella typhimurium

Abstract: Many bacteria secrete cellulose, which forms the structural basis for bacterial multicellular aggregates, termed biofilms. The cellulose synthase complex of Salmonella typhimurium consists of the catalytic subunits BcsA and BcsB and several auxiliary subunits that are encoded by two divergently transcribed operons, bcsRQABZC and bcsEFG. Expression of the bcsEFG operon is required for full-scale cellulose production, but the functions of its products are not fully understood. This work aimed to characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(60 citation statements)
references
References 95 publications
1
57
2
Order By: Relevance
“…For the first time, we show at the protein level that the C-terminal domain of BcsG is sufficient for pEtN transfer in vitro. Furthermore, Sun et al (27) demonstrated that the C-terminal domain of BcsG from Salmonella typhimurium is capable of cleaving pEtN-phospholipids, but evidence of transfer to a cellulose acceptor was not demonstrated. Our results further expand this data to include direct transfer of the pEtN group to cellooligosachharides by the BcsG C-terminal domain in the absence of Bcs proteins, which was only predicted from the model originally proposed (26).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the first time, we show at the protein level that the C-terminal domain of BcsG is sufficient for pEtN transfer in vitro. Furthermore, Sun et al (27) demonstrated that the C-terminal domain of BcsG from Salmonella typhimurium is capable of cleaving pEtN-phospholipids, but evidence of transfer to a cellulose acceptor was not demonstrated. Our results further expand this data to include direct transfer of the pEtN group to cellooligosachharides by the BcsG C-terminal domain in the absence of Bcs proteins, which was only predicted from the model originally proposed (26).…”
Section: Resultsmentioning
confidence: 99%
“…The specific role of BcsG has been proposed as a pEtN transferase directly modifying the cellulose polymer, although its sufficiency to do so has not before been demonstrated. Sun et al have shown BcsG exhibits phospholipase activity, fulfilling at least part of its proposed role in pEtN cellulose biosynthesis (27). Furthermore, the structure of the C-terminal catalytic domain from Salmonella typhimurium was also reported by Sun et al (PDB id 5OLT) and site-directed mutagenesis studies of a limited set of residues reflected particular phenotypes pointing to the importance of bcsG to the pEtN cellulose biofilm.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…The gene bcsC is involved in helping the biosynthetic release of cellulose by encoding a protein that forms the pore in the outer membrane [ 13 ]. Recently, the bcsG gene has been characterised as encoding a Zn 2+ -dependent phosphoethanolamine transferase, which has a crucial role in cellulose formation and maintenance of biofilm integrity [ 29 ]. However, the function of the gene bcsF is not understood yet.…”
Section: Discussionmentioning
confidence: 99%